Modern Approaches to Treatment Endometrioid Ovarian Cysts - Zhumaeva D. R (American Journal of Bioscience and Clinical Integrity, 2025)
Endometrioid cysts are one of the most frequently diagnosed manifestations of endometriosis. Endometrioid cysts are found in 10–14% of women who have undergone surgery for various pelvic masses. An endometrioid cyst can be from 0. 5 to 10 cm in size, develop asymptomatically or with vivid clinical manifestations resembling the clinic of "acute abdomen". Ovarian damage by endometriosis is accompanied by local inflammatory changes, hormonal status disorders, and a decrease in the patient's quality of life. Endometrioid ovarian cysts, commonly associated with endometriosis, represent a significant gynecological concern affecting women's reproductive health and quality of life. These cysts are characterized by the presence of endometrial-like tissue within the ovary, often leading to chronic pelvic pain, infertility, and hormonal disturbances. Despite advancements in diagnostic techniques, the management of endometrioid cysts remains challenging due to high recurrence rates and the need to balance effective treatment with ovarian preservation, especially in women of reproductive age. This review identifies a critical knowledge gap in integrating individualized and fertility-preserving approaches into the standard care of patients with endometrioid ovarian cysts. A narrative literature review was conducted by analyzing recent peer-reviewed studies from 2015 to 2024, focusing on surgical, medical, and emerging therapies. Findings indicate that while laparoscopic cystectomy remains the gold standard for surgical management, it carries a risk of reducing ovarian reserve. Hormonal therapies such as progestins, combined oral contraceptives, and GnRH agonists have shown efficacy in symptom control and recurrence prevention. Recent innovations, including selective progesterone receptor modulators and anti-angiogenic agents, are being explored for their potential to offer targeted, less invasive treatment options. The results underscore the necessity of individualized treatment strategies based on age, symptom severity, reproductive plans, and cyst characteristics. Future research should focus on long-term outcomes of novel therapies, biomarkers for recurrence prediction, and comparative studies evaluating fertility outcomes, with the goal of optimizing both clinical efficacy and patient quality of life in the management of endometrioid ovarian cysts.